SOCIAL MEDIA AS A PLATFORM FOR ARABIC LEARNING: EXPLORING OPPORTUNITIES AND CHALLENGES IN THE DIGITAL ERA: WASĀʾIL AT-TAWĀṢUL AL-IJTIMĀʿĪ KAMANṢṢAH LITAʿALLUM AL-LUGHAH AL-ʿARABIYYAH: ISTIKSHĀF AL-FURAṢ WA AT-TAḤADDIYĀT FĪ AL-ʿAṢR AR-RAQAMĪ - Aifanisa Rahman; Annisa Juliarti; Anggun Khairani; Suci Ramadhanti Febriani (Program Studi Bahasa dan Sastra Arab STIABI Riyadul 'Ulum, 2025)
The digital era has brought significant transformations to education, including Arabic language learning in Indonesia. The integration of technology, particularly social media, has opened vast opportunities to enhance accessibility, efficiency, and interactivity in the learning process. Social media features, such as interactive discussions through WhatsApp groups and live comments on Instagram, enrich the learning experience. However, optimizing social media for Arabic learning also presents challenges, such as technological dependency, distractions, and privacy issues. This research employs a qualitative approach with a literature review design to analyze the role of social media in Arabic language learning in the digital era. The findings indicate that social media supports community-based learning, innovative teaching materials, and individual needs adaptation. Nonetheless, addressing challenges requires actions like developing digital curricula, standardizing content, and improving digital literacy for educators and students. These strategies are essential to harness social media's potential optimally while mitigating risks. Overall, social media holds great potential as a catalyst for Arabic language learning. With the right approach, social media can become not only a supplementary tool but also an integral part of modern learning strategies, effectively supporting Arabic proficiency.